Accessory cardiac bronchus with associated lung parenchyma: rare congenital tracheobronchial anomaly: Accessory Cardiac Bronchus - Kuhtić, Ivana; Marušić, Ante; Krešić, Elvira; Mandić, Tinamarel; Coce, Neva; Butorac Petanjek, Bojana; Badovinac, Sonja; Lovrec, Petra (Acta Biomedica Atenei Parmensis, 2023)
Accessory cardiac bronchus (ACB) has been described mainly as case reports finding (frequency 0.08%-0.39%). Even though 50% of all ACBs have a blind extremity, imaging studies have demonstrated that some develop into a series of bronchioles with cystic degeneration or a ventilated lobule demarcated by an anomalous fissure and extremely rare with an abnormal pulmonary artery. In this case, ACB was demonstrated on several imaging methods arising from the intermediate bronchus’s medial wall with correspondent blood vessels and fissure. Although an ACB is not a pathological entity and most patients with ACB are asymptomatic, it can become symptomatic due to recurrent infection, empyema, hemoptysis, and malignant transformation. In conclusion, both pulmonologists and radiologists should recognize normal bronchial anatomy and developmental bronchial anomalies, as these may be important to establish a correct diagnosis.